2019
DOI: 10.1039/c9nr03710a
|View full text |Cite
|
Sign up to set email alerts
|

Diamond nano-optode for fluorescent measurements of pH and temperature

Abstract: Nano-optodes with a diamond core coated with a double stimuli-responsive polymeric shell reversibly respond to pH and temperature changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Compared to previous reports on ND pH sensing, our technique is considerably simpler as it does not require ND polymer coating or a microwave generator for spin state manipulation. 27,31,54 Our demonstration of pH direct reporting at a single-particle level (Fig. 5c) opens the possibility to perform pH nanosensing experiments (such as pH mapping inside living cells) using single-particle tracking.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Compared to previous reports on ND pH sensing, our technique is considerably simpler as it does not require ND polymer coating or a microwave generator for spin state manipulation. 27,31,54 Our demonstration of pH direct reporting at a single-particle level (Fig. 5c) opens the possibility to perform pH nanosensing experiments (such as pH mapping inside living cells) using single-particle tracking.…”
Section: Discussionmentioning
confidence: 88%
“…Characterization methods are also essential for new ND bio-sensing assays. For instance, Raabova et al showed that the charge state of a NV center in polymer-coated NDs could be used to detect pH changes; 31 this was achieved by measuring changes in the ND's emission spectra to differentiate the two photoactive charge states of the NV center (NV − and NV 0 ; NV + is non-photoactive), since NV 0 has its emission 60 nm blue-shifted compared to NV − (see Fig. 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has also been demonstrated that nanodiamonds containing nitrogen-vacancy (NV) centres can be used to sense their magnetic surroundings with unprecedented sensitivity with nanoscale resolution [ 17 , 18 ]. When combined with pH-responsive polymers, their location can imply intracellular pH changes [ 19 ]. Charge conversion of NV centres can also be used as an indicator for pH but requires complex equipment for readout [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the particle variations, it seems necessary to calibrate dD/dT in situ prior to the target measurement, as performed in the case of other fluorescence nanothermometers [31,166,167]. Further, this strategy for particle calibration is expected to be common to all types of ND family, such as critically magnetic coupled NDs [49] and chemically functionalized NDs [168,169], because these additional coupling components likely increase the inhomogeneity in dD/dT .…”
Section: Temperature Dependencementioning
confidence: 99%